Key Principles for Managing Recovery of Kelp Forests through Restoration. (8th July 2020) - Morris, Rebecca L; Hale, Robin; Strain, Elisabeth M A; Reeves, Simon E; Vergés, Adriana; Marzinelli, Ezequiel M; Layton, Cayne; Shelamoff, Victor; Graham, Tristan D J; Chevalier, Mathilde; Swearer, Stephen E
Abstract: There is increasing interest in mitigating the loss of kelp forests through restoration, but this has received scant attention relative to other coastal habitats. We evaluate current knowledge centered on key restoration principles to provide guidelines for best practice in kelp restoration. The cause and scale of degradation is fundamental in determining if kelp can be restored and the methods required to promote reestablishment. Removal of stressors may be adequate to achieve restoration goals where degradation is not too widespread or acute. Extensive losses of kelp forests will often require active reseeding of areas because of the low dispersal ability of many kelp species. Restoration efforts have generally taken a trial-and-error approach at experimental scales to develop techniques for establishing individuals. Furthermore, studies that inform cost–benefit analysis and the appropriate spatial scales for restoration of sustainable kelp forests are urgently needed for prioritizing and scaling up restoration efforts globally.